Analisis Semantik Teks Agama Buddha : Makna, Simbolisme, dan Interpretasi Hermeneutik - Kartini Kartini (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
The semantic study of religious texts is becoming increasingly important in understanding the meaning of spiritual teachings in a deep, contextual, and relevant way to current developments. This article aims to analyze the semantic aspects of Buddhist texts, emphasizing the meaning, symbolism, and interpretation of key terms. This study uses a descriptive qualitative approach with a hermeneutic method to examine key concepts such as dukkha, nirvana, and samsara found in classical Buddhist texts, including the Dhammapada, the Lotus Sutra, and the Abhidhamma. The analysis shows that the meaning of terms in Buddhist texts is not static or merely literal, but rather contains symbolic, philosophical, and spiritual dimensions that develop according to cultural, social, and historical contexts. These findings confirm that a semantic approach can enrich the understanding of Buddhist teachings, broaden the horizons of religious interpretation, and bridge the relevance of Buddhist values ​​in modern human life.